2018
DOI: 10.1111/1365-2435.13201
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and the physiological niche are co‐adapted in a desert‐dwelling lizard

Abstract: A major goal of seasonal biology is to understand how selection on phenology and the physiological niche interact. In oviparous species, fitness variation across the growing season suggests that phenological shifts will alter selective environments experienced by embryos. We hypothesize that physiology could become co‐adapted with phenology; such that embryos perform better in the environmental conditions they are adapted to compared to embryos adapted to other environments (temporal matching). Here, we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 63 publications
1
41
1
Order By: Relevance
“…We multiplied by flow rate to get V CO 2 and V O 2 per min, expressed by mL g −1 min −1 (e.g. Lighton, 2018;Sun et al, 2018).…”
Section: Metabolic Modifications Hypothesismentioning
confidence: 99%
“…We multiplied by flow rate to get V CO 2 and V O 2 per min, expressed by mL g −1 min −1 (e.g. Lighton, 2018;Sun et al, 2018).…”
Section: Metabolic Modifications Hypothesismentioning
confidence: 99%
“…Second, if a warming climate has negative effects on offspring as shown in some other lizards [ 42 , 43 ], then parents and offspring would perform worse overall in the warming climate than in the present climate. Third, if parents are capable of adjusting offspring phenotype via predictive adaptive plasticity, offspring would perform better in thermal environments similar to that of their parents, as suggested by the environmental matching hypothesis [ 25 , 48 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have demonstrated that egg mass can vary seasonally and affect offspring phenotypes in this species (Sun et al . 2018) and other reptiles as well (Ji & Braña 2000; Du et al . 2014; Mitchell et al .…”
Section: Discussionmentioning
confidence: 99%